2020
DOI: 10.1074/jbc.ra120.012722
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of the microbial stress protectants and chemical chaperones ectoine and hydroxyectoine by a bacterial hydrolase–deacetylase complex

Abstract: When faced with increased osmolarity in the environment, many bacterial cells accumulate the compatible solute ectoine and its derivative 5-hydroxyectoine. Both compounds are not only potent osmostress protectants, but also serve as effective chemical chaperones stabilizing protein functionality. Ectoines are energy-rich nitrogen and carbon sources that have an ecological impact that shapes microbial communities. Although the biochemistry of ectoine and 5-hydroxyectoine biosynthesis is well understood,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(59 citation statements)
references
References 74 publications
3
56
0
Order By: Relevance
“…However, their occurrence in Archaea is restricted (Czech et al 2018a;Kunte et al 2014;Pastor et al 2010;Widderich et al 2016a) (Figure 2). Building on recent searches of the IMG/MER database of microbial genomes and metagenomic assemblies (Chen et al 2019), and considering only fully sequenced bacterial and archaeal genomes (Czech et al 2018a;Mais et al 2020), the distribution of the ectoine biosynthetic genes in 8 850 fully sequenced genomes (8557 Bacteria and 293 Archaea) was assessed ( Figure 2). In this dataset, 665 predicted ectoine producers originated from Bacteria while 11 representatives belong to the Archaea (Supplementary Figure S1).…”
Section: Phylogenomic Distribution Of Ectoineproducing Microorganismsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, their occurrence in Archaea is restricted (Czech et al 2018a;Kunte et al 2014;Pastor et al 2010;Widderich et al 2016a) (Figure 2). Building on recent searches of the IMG/MER database of microbial genomes and metagenomic assemblies (Chen et al 2019), and considering only fully sequenced bacterial and archaeal genomes (Czech et al 2018a;Mais et al 2020), the distribution of the ectoine biosynthetic genes in 8 850 fully sequenced genomes (8557 Bacteria and 293 Archaea) was assessed ( Figure 2). In this dataset, 665 predicted ectoine producers originated from Bacteria while 11 representatives belong to the Archaea (Supplementary Figure S1).…”
Section: Phylogenomic Distribution Of Ectoineproducing Microorganismsmentioning
confidence: 99%
“…These numbers are for obvious reasons only fleeting snapshots. Given that incompletely sequenced microbial genomes and metagenomic sequences were not taken into account, it is highly likely that the number of microbial ectoine producers will considerably exceed the number derived from the inspection of only fully sequenced microbial genomes (Mais et al 2020). Studies on the taxonomic affiliation of ectoine-synthesizing microorganisms revealed their presence in 10 bacterial and two archaeal phyla ( Figure 2).…”
Section: Phylogenomic Distribution Of Ectoineproducing Microorganismsmentioning
confidence: 99%
See 3 more Smart Citations